Peran Motivasi dan Penilaian SOTH terhadap Kinerja BKB Kartini di Kelurahan Bandungrejosari, Sukun Kota Malang - Made Iska Aprilita Wardani; Pudji Lestari; Dewi Retnowati; Kristin Juwita (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Motivation and assessment are ways to determine the results of program work both individually and in general for the organization as a whole. The research method is Paired Sample Test, namely comparing the roles before and after the roles of Motivation and SOTH Assessment. Meanwhile, qualitatively, skills are assessed, namely consisting of coordination and teamwork abilities; discipline and solutions to problems. Assessment data from January to March 2024. The time limit was chosen due to ongoing program adjustments. The research results show that SOTH motivation and assessment have an average impact of 26% and make motivation and assessment more attention to all members of the organization. Based on the Paired Sample Test, it can be concluded that from the Paired Sample Test calculations it is proven that there is a significant difference in the average role of Motivation and Assessment before and after the delivery of the material begins (Pre Test) for the participants (students) at a confidence level of 95%. And proves that motivation and assessment are useful for program efficiency and effectiveness, controlling and monitoring performance, and are able to encourage participants (students), managers and presenters to contribute to even better performance.